WIND POWER IN SWEDEN - Bottlenecks, Barriers, and Potentials - Jakobson, Amelie; Wang, Lucas; Sjöö, Elsa; Sjökvist, Tilde; Munther, Gustaf (My University, 2026)
Wind power development is coming to a halt in 2027. Simultaneously, southern parts of Sweden are experiencing relatively high electricity prices. In an era of electrification and energy scarcity, why is the development of wind power ceasing? This paper provides a systematic overview of wind power development in Sweden by examining current trends, key challenges and regulatory, economic and social barriers affecting further expansion. In addition, the study includes potential benefits and opportunities associated with continued wind power development, as well as the conflicts and trade offs embedded in proposed solutions to these barriers. Using a mixed-method approach, the study combines a literature study and interviews with relevant stakeholders. The literature study contributes to the understanding of how wind power projects are planned, assessed and developed, while the interviews offer insights of the barriers, conflicts and differing perspectives among actors involved in the process. The findings indicate that the main barriers to wind power development include the municipal veto, restrictions related to national security, local opinion influenced by misinformation, uncertainties within the permitting process and politic polarisation. However, a broader range of respondents and a larger number of interviews would have been desired for a more balanced and universal perspective. Together, these barriers interact to create a system in which further development is essentially impossible, as conflicting interests and institutional uncertainties continue to hinder expansion.